2019
DOI: 10.1007/s00467-019-04430-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term all-cause mortality and cardiovascular outcomes in Scottish children after initiation of renal replacement therapy: a national cohort study

Abstract: Background Data on long-term outcomes in children who have received renal replacement therapy (RRT) for end-stage renal disease are limited. Methods We studied long-term survival and incidence of fatal and nonfatal cardiovascular disease (CVD) events and determinants of these outcomes in children who initiated RRT between 1961 and 2013 using data from the Scottish Renal Registry (SRR). Linkage to morbidity records was available from 1981. Results A total of 477 children of whom 55% were boys, almost 50% had co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…While this incident rate is much higher than the general population, it is not as high as the rates reported in other ESKD cohorts. By comparison, a recent study of a Scottish population who had commenced RRT during childhood reported an ~55% higher incidence of cardiovascular events compared with our cohort 9 . Notably the Scottish cohort had a crude overall mortality rate 25% greater than our Australian cohort which is likely to also account for some of the difference.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…While this incident rate is much higher than the general population, it is not as high as the rates reported in other ESKD cohorts. By comparison, a recent study of a Scottish population who had commenced RRT during childhood reported an ~55% higher incidence of cardiovascular events compared with our cohort 9 . Notably the Scottish cohort had a crude overall mortality rate 25% greater than our Australian cohort which is likely to also account for some of the difference.…”
Section: Discussioncontrasting
confidence: 83%
“…The discrepancy in the type of outcome associated each variable cannot be readily explained. Lack of transplant during follow‐up was also identified by Galiyeva et al as a vascular risk factor 9 . In Australia, deceased donor transplant allocation bonuses have been available to those less than 18 years of age from 2000.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Kidney transplantation (KT) is the treatment of choice for children with end-stage kidney disease (ESKD) as it offers better survival and quality of life compared to treatment with dialysis ( 1 , 2 ). Preemptive kidney transplantation (PKT) is performed before the initiation of dialysis to avoid the morbidity and mortality associated with dialysis ( 3 , 4 ). Whether or not PKT also leads to improved clinical outcomes has been addressed by several studies but these report mixed findings.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, both the prevalence and incidence of chronic kidney disease (CKD) in children have increased ( 1 ). Unlike adult patients, the most common causes of CKD in children are congenital malformations; but the increase in overweight/obesity in children may be a contributing factor as well ( 2 ).…”
Section: Introductionmentioning
confidence: 99%